Changes of median nerve conduction, cross-sectional area and mobility by radioulnar wrist compression intervention in patients with carpal tunnel syndrome - Yifei Yao; Emily Grandy; Lenicia Jenkins; Juliet Hou; Peter J. Evans; William H. Seitz, Jr; Zong-Ming Li (Journal of Orthopaedic Translation, 2019)
Background: Owing to the compressive nature of the neuropathy, patients with carpal tunnel syndrome (CTS) have prolonged distal motor latency (DML), sensory nerve latency (SNL), median nerve swelling and restricted median nerve mobility. The purpose of this study was to noninvasively augment carpal tunnel space using radioulnar wrist compression (RWC) and evaluate its effects on median nerve pathological properties in patients with CTS. It was hypothesized that the RWC intervention would reduce the median nerve DML, SNL and cross-sectional area (CSA) and enhance longitudinal median nerve mobility in patients. with CTS. Methods: Eleven patients diagnosed with CTS participated in this study. A portable RWC intervention splint was developed to apply 10 N of compressive force across the wrist. Three daily sessions of RWC were performed over 4 weeks of intervention (15 min per session, 45 min per day, 7 days per week). Each 15-min session consisted of three 5-min blocks of RWC, with a 1-min rest in between consecutive blocks. Patients were evaluated at Week 0 (baseline), Week 2 (mid-intervention) and Week 4 (end of intervention). DML and SNL of the median nerve were evaluated using established nerve conduction study techniques. Median nerve CSA at the distal wrist crease was obtained by ultrasound imaging. Median nerve motion associated with finger flexion/extension was captured by dynamic ultrasound imaging and quantified using a speckle cross-correlation algorithm. Finger flexion/extension was recorded using an electrogoniometer. The slope of the regressed linear equation of median nerve displacement as a function of finger flexion angle was used to quantify nerve mobility. Results: Patients with CTS showed significantly decreased DML (p = 0.048) and median nerve CSA (p < 0.001) and increased nerve mobility (p < 0.001) at mid-intervention compared to baseline. However, DML, CSA and mobility of the median nerve did not differ significantly between Weeks 2 and 4 (p = 0.574, 1.00 and 0.139, respectively). Median nerve SNL was not significantly affected throughout the 4-week intervention (p = 0.330 for Week 0 vs. 2; p = 1.00 for Week 2 vs. 4). Conclusion: This study revealed that RWC intervention with 10-N force applied to the wrist in the radioulnar direction could restore impaired neurophysiological and biomechanical functions of the median nerve. The beneficial effects of RWC intervention for the median nerve were in evidence after a relatively short period of two weeks. These functional improvements could be explained by intermittent decompression of the median nerve via RWC-induced augmentation of the carpal arch. The translational potential of this article: Biomechanically manipulating the carpal tunnel by RWC decompresses the median nerve and has the potential to become an alternative treatment for CTS. Keywords: Carpal tunnel syndrome, Cross-sectional area, Median nerve, Mobility, Nerve conduction, Radioulnar wrist compression